Analisis Ketimpangan Antarwilayah dan Pergeseran Struktur Ekonomi di Kalimantan: Analysis of Across Region Inequality and Economic Structure Shift in Kalimantan - Pratiwi, Maria Christina Yuli (Pusjar SKPP Lembaga Administrasi Negara, 2021)
Inequality is a common problem in development, including in Indonesia. The development of Kalimantan is inseparable from the problem of inequality. This study aimed to analyze the uneven development across districts and economic structure shift of 56 districts, also to prove the capability of Kuznets Hypothesis in Kalimantan during 2012-2019. This study used secondary data which was processed by Williamson Index, Entropy Theil Index, Pearson Correlation, and Shift Share analysis. The result of study showed that: (1) regional inequality in Kalimantan is high but shows decreasing trend for the period of observation; (2) inequality between regions in Kalimantan is more caused by inequality between provinces. Province of East Kalimantan provides the largest contribution towards the inequality between and within provinces; (3) There is a strong relationship between the variable of per capita GRDP and the inequality index. Meanwhile, the relationship between the economic growth variable and the inequality index is less strong; (4) Kuznets hypothesis is not applicable in Kalimantan; (5) and the economic structure of Kalimantan has shifted from the agricultural sector to the industrial sector. Ketimpangan merupakan permasalahan umum dalam pembangunan, tidak terkecuali di Indonesia. Pembangunan wilayah Kalimantan juga tidak terlepas dari masalah ketimpangan. Penelitian ini bertujuan untuk menganalisis ketidakmerataan pembangunan antarwilayah dan pergeseran struktur ekonomi di 56 kabupaten/kota, serta membuktikan Hipotesis Kuznet berlaku atau tidak di Kalimantan selama periode 2012–2019. Studi ini menggunakan data sekunder yang diolah dengan analisis Indeks Williamson, Indeks Entropi Theil, Korelasi Pearson, dan Shift Share. Hasil penelitian menunjukkan bahwa: (1) ketimpangan antarwilayah di Kalimantan tergolong tinggi dengan tren yang cenderung menurun; (2) ketimpangan antarwilayah di Kalimantan lebih diakibatkan oleh ketimpangan antar provinsi. Provinsi Kalimantan Timur memberi sumbangan terbesar terhadap ketimpangan antar dan dalam provinsi; (3) Terdapat hubungan yang kuat antara variabel PDRB per kapita dan indeks ketimpangan. Sedangkan hubungan antara variabel pertumbuhan ekonomi dengan indeks ketimpangan kurang kuat; (4) Hipotesis Kuznets tidak berlaku di Kalimantan; dan (5) struktur ekonomi Kalimantan mengalami pergeseran dari sektor pertanian ke sektor industri.